Urgensi Komunikasi dalam Menumbuhkan Motivasi dalam Pembuatan Produk Newklin - Nisaa, Diva Khoirun; Fiernaningsih, Nilawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Communication between work groups is persuasive communication, face-to-face, to arouse passion and activity at work. The purpose of this paper is to describe how the urgency of communication in fostering the motivation of a work group or work group in developing a product. Type and research approach This type of research is a literature and field analysis study using qualitative methods. Qualitative research used by researchers is descriptive data, namely in the form of written or spoken words from people and observable behavior. Researchers use a qualitative approach because researchers are interested in a phenomenon in the field by collecting data through interview and observation techniques. The results of this study are, communication has several variables that can motivate the work of the work group, namely the relationship between superiors and subordinates, relationships among coworkers, company rules and policies, working conditions, and compensation. The communication that most quickly fosters motivation is the relationship between superiors and subordinates. The reason is that the supervisor is the one who must be able to motivate the work of the work group working in his company and maintain good working and communication relationships with the work group, if this does not happen, there is a high probability of massive changes in the work group structure. Communication with motivation is closely related to work group performance in achieving company goals. Keywords: Communication Urgency; Motivation; Work Group; Newklin Soap